Correlates of pume-livestock conflicts in the Espinal of Central Argentina - Lucherini, Mauro (2014)
Puma (Puma concolor) still has a widespread distribution in Argentina. However, many populations are threatened by habitat destruction and direct killing associated to the spreading of croplands and ranchlands. This is the case of pumas inhabiting the Espinal of the central Argentina lowlands, an ecoregion marking the transition from the Pampas grasslands, where the puma has almost gone extinct, to the Monte woodlands. In this region, the intense fragmentation of natural habitats and decrease of native prey has increased the encroachment of pumas with livestock. Retaliatory killing, which is the common response to puma predation on cattle, is increasing and local ranchers are requesting a legal bounty system to hunt pumas. We report the results of the first steps of a project aiming to understand the ecology of puma populations in the Espinal, characterize puma-livestock conflicts, and identify conflict mitigation strategies. 148 semi-structured interviews to local ranchers show that 45.7% of respondents think that pumas cause major damage, 47.5% reported losses caused by pumas in the previous year and 70.2% considered that predator control was the best solution to conflicts. Landscape-scale camera trap surveys (totaling an effort of 7054 trap-days) produced 45 records of pumas in 11.5% of 184 sampling stations. A preliminary habitat suitability analysis based on 110 presence records suggests that most suitable locations for puma were away from cropland or urban areas and from the main roads, distances to roads and to scrubland patches were the variables affecting the most its niche breadth, and only 16.3% of the region has a high quality for this felid. Our results suggest that whereas pumas in central Argentina may tolerate some degree of habitat degradation and human-related mortality, humans are rarely willing to tolerate economic losses caused by depredation and that conflict mitigation measures are required to ensure puma conservation.